Illiberal Social Policy in Europe: When Policy Implementation Meets Welfare Ideas - Dorottya Szikra; Lauritz Autischer (Politics and Governance)
This article examines the role of social policy in the electoral success of illiberal political parties in Europe between 2010 and 2024, systematically comparing social policies of illiberal actors in Austria, Hungary, Italy, and Poland. Utilizing qualitative content analysis, we differentiate between the welfare ideas of illiberal parties and their actual policy implementations to understand the mechanisms behind their sustained popularity. We paid special attention to the link between ideas and policy reforms to understand whether illiberals carried out paradigmatic changes that altered the underlying goals of social policies. Our findings reveal that illiberal actors align their social policies with the welfare ideas they propagate, targeting specific demographic groups often neglected by earlier democratic politics. We observe that besides their exclusionary rhetoric and reforms against the “undeserving outsiders,” such as immigrants, illiberals implement paradigmatic inclusionary reforms, especially to social insurance systems. Notably, the consistency and ideological alignment of their social policies contribute significantly to building loyal constituencies and challenging previous welfare state arrangements. This study highlights the necessity of recognizing the complexity of illiberal social policy to fully grasp the dynamics of their political appeal and offers insights to liberal democratic actors on effective policy responses.